Usage of Hydrophobic Ionic Liquid [BMIM][PF6] for Recovery of Acid Dye from Wastewater and Sequential Application in Tussah Silk Dyeing. Issue 6 (4th October 2013) - Lin, Jie; Teng, Yi; Lu, Yanhua; Lu, Sheng; Hao, Xu; Cheng, Dehong
<x xml:space="preserve">Abstract</x> Hydrophobic ionic liquid 1‐butyl‐3‐methylimidazolium hexafluorophosphate ([BMIM][PF6]) was explored to recover weak acid blue 6B from dyeing wastewater via liquid–liquid extraction protocol. A recovery efficiency of ca. 95% was achieved when 1.0 mL of 0.016 g/L dye solution was directly extracted by 0.2 mL ionic liquid [BMIM][PF6] without using any extractions. Investigations of UV–Vis and FTIR spectra indicated that structure of weak acid blue 6B did not change after weak acid blue 6B was extracted into ionic liquid phase. The main driving force of extraction was that solubility of weak acid blue 6B in ionic liquid phase was more than that in aqueous phase. The collected [BMIM][PF6] including weak acid blue 6B was sequentially applied in Tussah silk dyeing process. The dyeing performances of silk with 0.5% w/w ionic liquid [BMIM][PF6] as retarding agent were the same as that with 10% w/w inorganic salt, which indicated that ionic liquid [BMIM][PF6] was an excellent retarding agent and could be used to displace traditional inorganic salt in silk dyeing. In the aspect of environmental protection, the used [BMIM][PF6] dosage was only twentieth of traditional inorganic salt, which shown great promise as an attractive alternative or replacement to traditional inorganic salts in silk dyeing.Photographs of an aqueous‐[BMIM][PF6] two‐phase system: (left) before extraction; (right) after extraction. Eleven dyes were directly extracted by using ionic liquid [BMIM][PF6] as extraction solution. The main driving force of extraction was the higher solubility of weak acid blue 6B in ionic liquid as in the aqueous phase.